2022
DOI: 10.3390/ijerph192214697
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Stiffness following Endurance and Resistance Exercise Sessions in Older Patients with Coronary Artery Disease

Abstract: Arterial stiffness (AS) is associated with coronary artery disease (CAD). Acute endurance training decreases AS, whereas acute resistance training increases it. However, these results are from studies in apparently healthy adults, and there is no information on the effects of such afterload AS in elderly patients with CAD. We aimed to investigate the effect of acute endurance or resistance training on the time course of changes in the indices of AS in elderly patients with CAD in order to understand how stiffn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Similar to our findings, several studies have demonstrated that peripheral distensibility is improved with high intensity exercises. However, this type of work also produces a marked decrease in central distensibility and an increase in central AS [ 25 , 26 , 27 ]. These are similar to the arterial response following dynamic muscle strengthening exercise [ 26 , 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to our findings, several studies have demonstrated that peripheral distensibility is improved with high intensity exercises. However, this type of work also produces a marked decrease in central distensibility and an increase in central AS [ 25 , 26 , 27 ]. These are similar to the arterial response following dynamic muscle strengthening exercise [ 26 , 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this type of work also produces a marked decrease in central distensibility and an increase in central AS [ 25 , 26 , 27 ]. These are similar to the arterial response following dynamic muscle strengthening exercise [ 26 , 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation